Pengaruh Budaya Organisasi dan Pelatihan Kerja Terhadap Kinerja Karyawan Pt Pos Indonesia Karawang - Gunawan Lesmana; Aji Tuhagana; Zenita Apriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
A positive organizational culture creates a work environment that supports growth, innovation, and collaboration. On the other hand, job training helps employees to develop the skills, insight and actions needed to produce maximum performance. The research carried out applied quantitative methods which aimed to observe the influence of organizational culture and job training on employee performance at PT Pos Indonesia Karawang. The data collected was carried out through the application of interview, observation and survey methods by distributing questionnaires to PT Pos Indonesia Karawang, totaling 75 employees. To all employees of PT POS Indonesia Karawang. The samples taken were carried out by purposive sampling. Based on the analytical tests produced on the variables of organizational culture and job training, it can be concluded that simultaneously the influence of job training on employee performance is found, which means that H3 is accepted.